Evolución satisfactoria de paciente con Síndrome de Pickwick post terapia bariátrica endoscópica y soporte ventilatorio - Saenz, Hugo (2020)
Patient with Extreme Obesity (Body Mass Index> 50Kg/m2) and comorbidities who came to our Institution in Respiratory Insufficiency and was treated ambulatory for the next 6 months with non-invasive ventilatory support and endoscopic placement of intragastric bariatric balloon. A reduction of 68% of Excess Body Mass Index and normalization of all respiratory and laboratory parameters was obtained at the end of the observation period.